Supramolecular architecture in some 4-halophenylboronic acids - Shimpi, Manishkumar R.; SeethaLekshmi, Nanappan; Pedireddi, Venkateswara Rao (Crystal Growth & Design, 2007)
Crystal structures of 4-chloro- and 4-bromophenylboronic acids (1 and 2) and hydrates of 2 and 4-iodophenylboronic acid in two different forms (2a, 3a, and 3b), which were characterized by single-crystal X-ray diffraction methods, are reported. In structures I and 2, -B(OH)2 forms a syn-anti conformation, but it exists in syn-syn as well as anti-anti conformations in the hydrated structures 2a, 3a, and 3b. In all the structures, the molecules are held together by O-H center dot center dot center dot O interactions formed by -B(OH)2 groups. The C-H center dot center dot center dot X (X = Cl, Br, and I) interactions play an important role in crystal packing. In 2, Br center dot center dot center dot Br interactions are also observed. Interestingly, all the three hydrates form similar types of three-dimensional structures with the formation of channels, which are occupied by water molecules. The two hydrates of 4-iodophenylboronic acid (3a and 3b) are distinguishable on the basis of O center dot center dot center dot O short contacts, with an identical host lattice of the boronic acid.